2010
DOI: 10.1177/1063293x10379765
|View full text |Cite
|
Sign up to set email alerts
|

Petri Net-based Coordination Component for Collaborative Design

Abstract: Considering the lack of efficient coordination of task interdependencies in a collaborative design system, the temporal and resource coordination mechanisms for the problems in our investigation are established based on Petri Nets. The whole system could be expanded as a Petri Net for simulation and analysis. The architecture of reusable and pluggable components is also introduced to implement such mechanisms. The proposed approach offers strong support for the performance evaluation of the collaborative desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The main difference between collaborative and collective design lies within the structuredness of the knowledge and the means of communication. In (Huang et al, 2010), authors distinguish the difference between 'tightly coupled collaborative design' -which requires project management tools and sophisticated coordination mechanisms among participants; and 'loosely coupled collaborative design' -which is based on social protocols and participants' abilities that do not require any explicit coordination. With the rise of the internet, loosely coupled collaborative networks such as Wikipedia (Panciera et al, 2009) have emerged, where people voluntarily self-organize and develop significant intellectual products as an expression of 'radically different types of collective intelligence' (Matthews et al, 2012).…”
Section: Background and Related Workmentioning
confidence: 99%
“…The main difference between collaborative and collective design lies within the structuredness of the knowledge and the means of communication. In (Huang et al, 2010), authors distinguish the difference between 'tightly coupled collaborative design' -which requires project management tools and sophisticated coordination mechanisms among participants; and 'loosely coupled collaborative design' -which is based on social protocols and participants' abilities that do not require any explicit coordination. With the rise of the internet, loosely coupled collaborative networks such as Wikipedia (Panciera et al, 2009) have emerged, where people voluntarily self-organize and develop significant intellectual products as an expression of 'radically different types of collective intelligence' (Matthews et al, 2012).…”
Section: Background and Related Workmentioning
confidence: 99%
“…To obtain the reliability of a complex system, the reliability model should be built to describe the failure logic relationship between the whole system and its compositions. In recent decades, various reliability modeling methods have been developed for complex systems, where some static and dynamic modeling techniques, including RBD model, fault tree (FT) model, binary decision diagrams model, Markov model, dynamic FT (DFT) model, and Petri net model have been applied.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Research in these non-military fields then provides some insight into approaches for integration. Emerging research in these areas indicates there is a connection between agreeing on a common conceptual model and the integration level of the resulting product [53], [54], [55]. In their research COA Action, Klein et al demonstrated that for experts in tactical decision making having a common conceptual model enables joint option awareness [56].…”
Section: Conceptual Models Planning and Designmentioning
confidence: 99%